Coordination within Conversational Agents with Multiple Sources - Matos, Vinícius Bitencourt; Grava, Ricardo; Tavares, Rodrigo; José, Marcos Menon; Pirozelli, Paulo; Brandão, Anarosa A. F.; Peres, Sarajane M.; Cozman, Fábio G. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2023: Anais do XX Encontro Nacional de Inteligência Artificial e Computacional, 2023)
Conversational agents can now operate with language models, rules, ontologies and varied other sources to provide smooth dialogue. However, the coordination of multiple sources in conversational agents is a challenge. We present a mechanism to effectively orchestrate multiple sources in a conversational agent, by relying on a client-server approach with an associated prompt generation module that deals with heterogeneous domain-oriented modules. As a detailed use case, we describe the architecture of a chatbot specialised in topics related to the Brazilian coast, and we study the benefits of our approach.